Combined fibrinolysis using reduced-dose alteplase plus abciximab with immediate rescue angioplasty versus primary angioplasty with adjunct use of abciximab for the treatment of acute myocardial infarction: Asia-Pacific Acute Myocardial Infarction Trial (APAMIT) pilot study - Wong, A. (2016)
10.1002/ccd.20101